Screening of In vitro α-amylase Inhibitory Activity of Wild Orchids of Nepal - Joshi, Pusp Raj; Joshi, Siddharaj; Paudel, Mukti Ram; Pant, Bijaya (Journal of Nepal Biotechnology Association, 2022)
Orchids are the source of compounds like phenols, alkaloids, phenanthrenes widely used as a therapeutic agent. Inhibition of pancreatic α-amylase could be a better therapeutic approach in decreasing levels of post-prandial hyperglycemia. This study aimed to evaluate α-amylase inhibition of some orchid species to assess their inhibitory potential on PPA (porcine pancreatic α-amylase). Methanol extracts of the whole plant of Gastrochilus distichus (GDW), the pseudobulbs of Otochilus albus (OAP), the whole plant of Papilionanthe uniflora (PUW), pseudobulbs of Eria graminifolia (EGP), the leaves and pseudobulbs of Pholidota articulata (PAL and PAP) and stems of Vanda cristata (VCS) were screened for their phytoconstituents and role in α-amylase inhibition by modified 3,5-Dinitrosalicylic acid method. V. cristata, E. graminifolia and G. distichus extract showed moderate inhibition of α-amylase with IC50 of 582.73 μg/ml, 710.89 μg/ml, 798.78 μg/ml respectively when compared to acarbose (26.85 μg/ml). Phytochemical analysis revealed the presence of alkaloids, tannins, glycosides, flavonoids, saponins and steroids with the major phytoconstituents. This study concluded that V. cristata, E. graminifolia and G. distichus exhibited moderate α-amylase inhibitory activity and they could be a potent source for antidiabetic phytochemicals.